EDUKASI GOLONGAN DARAH SEBAGAI UPAYA MENINGKATKAN KESADARAN SISWA SMA DALAM KESIAPAN DONOR DARAH - Satyadini, Mutimanda Dwi; Utami, Sri; Kurniawati, Heny; Kusumaningrum, Elizabeth Novi (Jurnal Abdi Insani, 2025)
It is very important for everyone to know their blood type, and blood type testing is essential to fulfill the need for blood transfusions. The main problem with blood transfusions and blood group testing is that most Indonesians still do not know their blood type. In addition, public awareness of the importance of blood group testing continues to increase. In this community service program, blood donor alert school means students who are aware, willing, and able to donate their blood quickly with blood type data. The first step is blood group identification. Blood donor alert schools have existed since the beginning. One of the partners in this service initiative is Al Syukro Universal Islamic High School. Blood group checks, counseling, and surveys to identify student characteristics are all part of the procedures used. The result of respondents' understanding was good at 73% before the blood type education to raise awareness of high school students about their readiness for blood donation; afterwards, 62% were good and 13% were excellent. In summary, this counseling activity helped students understand more about blood and blood type and prepared them to become blood donors. As a result, Al Syukro Universal Islamic High School has students who are ready to become blood donors.